Stability and Transport in Magnetic Confinement Systems - Weiland, Jan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Stability and Transport in Magnetic Confinement Systems provides an advanced introduction to the fields of stability and transport in tokamaks. It serves as a reference for researchers with its highly-detailed theoretical background, and contains new results in the areas of analytical nonlinear theory of transport using kinetic theory and fluid closure. The use of fluid descriptions for advanced stability and transport problems provide the reader with a better understanding of this topic. In addition, the areas of nonlinear kinetic theory and fluid closure gives the researcher the basic knowledge of a highly relevant area to the present development of transport physics.
Introduction -- Different Ways of Describing Plasma Dynamics -- Fluid Description of Low Frequency Perturbations in an Inhomogeneous Plasma -- Kinetic Description of Low Frequency Modes in Inhomogeneous Plasma -- Kinetic Descriptions of Low Frequency Modes Obtained by Orbit Averaging -- Low Frequency Modes in Inhomogeneous Magnetic Fields -- Transport, Overview and Recent Developments -- Instabilities Associated with Fast Particles in Tordoidal Confinement Systems -- Nonlinear Theory -- General References -- Answers to Exercises.
Keywords: Physics; Nuclear fusion; Physics; Plasma Physics; Nuclear Fusion; Nuclear Energy; Theoretical, Mathematical and Computational Physics